2007
DOI: 10.1208/pt0803064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitosan type on the properties of extruded pellets with low amount of microcrystalline cellulose

Abstract: The purpose of this research was to study the influence of type of chitosan with different molecular weights, ie, 190 and 419 kDa, on properties of pellets prepared by extrusion/ spheronization. The formulations, consisting of acetaminophen as model drug, chitosan, microcrystalline cellulose (MCC), and dibasic calcium phosphate dihydrate with/without sodium alginate, were extruded using a twin-screw extruder and water as the granulating liquid. With 30% wt/wt MCC and no added sodium alginate, spherical pellets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…It was indicated that an increase in SA fraction led to an increase in pellet strength. Similar to our previous study, 17 the stronger pellets could be obtained by using lower molecular weight chitosan with addition of an appropriate amount of SA. It was suggested that the lower molecular weight chitosan with added SA provided the wet mass with more rigidity and plasticity, thus stronger pellets could be formed.…”
Section: Crushing Forcesupporting
confidence: 81%
See 3 more Smart Citations
“…It was indicated that an increase in SA fraction led to an increase in pellet strength. Similar to our previous study, 17 the stronger pellets could be obtained by using lower molecular weight chitosan with addition of an appropriate amount of SA. It was suggested that the lower molecular weight chitosan with added SA provided the wet mass with more rigidity and plasticity, thus stronger pellets could be formed.…”
Section: Crushing Forcesupporting
confidence: 81%
“…15,17 Moreover, both CSLW and CSHW exhibited a similar effect on the crushing force of pellets (Fig. 6).…”
Section: Crushing Forcementioning
confidence: 67%
See 2 more Smart Citations
“…Ph., USP, JP] (4). MCC, the gold standard for extrusion-spheronization, is widely used, but possesses various disadvantages, such as drug adsorption to the surface of its fibers, its chemical incompatibility with a number of drugs, and its lack of disintegration when used in matrix pellets (5)(6)(7)(8). Isomalt, a polyol produced from sucrose, is a novel potential carrier core exhibiting multiple health benefits as having low glycemic and low insulinemic responses, and thus is suitable for diabetics (9).…”
Section: Introductionmentioning
confidence: 99%